A model for the strain rate dependent plasticity of a metastable austenitic stainless steel. (15th September 2016) - Isakov, M.; May, M.; Hiermaier, S.; Kuokkala, V.-T.
Abstract: A continuum material model is developed for the dynamic plastic deformation behavior of metastable austenitic stainless steel EN 1.4318-2B. An incremental approach in both experimental testing and in the model is used to distinguish between the direct effects of strain rate and the macroscopic adiabatic heating effects. In the model a set of evolution equations is integrated over the deformation path, which makes the model flexible in terms of changes in the strain rate and material temperature. The strain-induced phase transformation from austenite to α′-martensite is accounted for with evolution equations based on the Olson-Cohen transformation model. In order to describe the phase transformation accurately during dynamic loading, the original model is modified by adding instantaneous strain rate sensitivity to the α′-transformation rate. Comparison with experimental results shows that the model can be used to describe the strain rate and temperature dependent behavior of a metastable austenitic alloy with a reasonable number of material parameters. Finally, the model gives realistic results in a set of validation experiments. Graphical abstract: Highlights: Strain rate history effects in metastable austenitic stainless steels are in this study shown to be notable. An internal variable based constitutive model that contains reasonable amount of parameters is developed. The effects of strain rate and adiabatic heating on material plasticity are separated by using strain rate jump experiments. Model is successfully verified with experimental data involving strong thermomechanical coupling.